The Case for Pragmatic Evidence-Based Higher Education: A Useful Way Forward? - Newton, Philip M.; Da Silva, Ana; Berry, Sam (Frontiers in Education, 2020)
Arguments for and against the idea of evidence-based education have occupied the academic literature for decades. Those arguing in favour plead for greater rigour and clarity to determine “what works”. Those arguing against protest that education is a complex, social endeavour and that for epistemological, theoretical and political reasons it is not possible to state, with any useful degree of generalisable certainty, “what works”. While academics argue, policy and practice in Higher Education are beset with problems. Ineffective methods such as ‘Learning Styles’ persist. Teaching quality and teacher performance are measured using subjective and potentially biased feedback. University educators have limited access to professional development, particularly for practical teaching skills. There is a huge volume of higher education research, but it is disconnected from educational practice. Change is needed. We propose a pragmatic model of Evidence-Based Higher Education, empowering educators and regulators to make judgements about the application of the most useful research evidence in a particular context, including pragmatic considerations of cost and other resources. Implications of the model include a need to emphasise pragmatic approaches to research in higher education, delivering results that are more obviously useful, and a pragmatic focus on practical teaching skills for the development of educators in Higher Education.